Three-year-cohort-study: clinical and cost effectiveness of an inpatient psychiatric rehabilitation - Awara, Mahmoud A.; Downing, Laura M.; Edem, Dorothy; Lewis, Norma; Green, Joshua T. (Frontiers in Psychiatry, 2023)
Introduction: There has been a resurgence of interest in psychiatric rehabilitation to cater to patients with chronic and complex mental illnesses. Aims: This study is aimed at examining patients’ characteristics and the prevalence of psychiatric and non-psychiatric comorbidity in a local inpatient rehabilitation service investigating the impact of the whole-system approach of rehabilitation on future utilization of mental health services, and analyzing the cost effectiveness and quality of this service. Method: Patients managed over a three-year period in a psychiatric rehabilitation inpatient unit were self-controlled; they were retrospectively (pre-rehabilitation) and prospectively (post-rehabilitation) examined for readmission rate, Length of Stay (LOS), and Emergency Room (ER) visits. Relevant information was retrieved from Discharge Abstract Database (DAD), Patient Registration System (STAR), and Emergency Department Information System (EDIS). The quality of care on the rehabilitation unit was examined using the Quality Indicator for Rehabilitative Care (QuIRC) and the cost analysis was conducted using data obtained from a single-payer government Medical Service Insurance (MSI) billing system. Results: Of the 185 patients admitted over the study period, 158 were discharged. There was a significant reduction of readmission rate (64% decrease), LOS (6,585 fewer days spent in hospital), and ER presentations (166 fewer visits) P < 0.0001 respectively. There was a substantial subsequent cost savings in the post-rehabilitation year.